Ileocecal intussusception in a patient with ileal melanoma metastasis: clinical case and review of the literature - M. A. Danilov; A. O. Atroschenko; S. V. Pozdnyakov; G. G. Saakyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of clinical case presentation. Choice of optimal surgical approach for treatment of intestinal intussusception. Key points. Intestinal intussusception is a rare condition, especially in adults, which can develop due to both benign and malignant neoplasms. Commonly intestinal intussusception is an accidental diagnostic finding, however cases of clinically severe intussusception resulting in impaired passage of intestinal content are described in the literature. Ultrasound investigation and endoscopy contribute significantly to diagnosis of this pathology; however in certain cases computer and magnetic-resonance tomography are required. Surgical approach in intestinal intussusception varies widely from conservative reposition of intussuscepted loop to expanded resection of intestinal segment. Clinical case of ileocecal intussusception caused by melanoma metastasis to the ileum is presented.